Homestays as a resource for preservice teachers studying abroad. (November 2022) - Back, Michele; Joseph, Rebecca; McCormick, Anna; Picorelli, Hana
Abstract: Although the literature on educators studying abroad points to the importance of community and other non-classroom interactions, no study has examined how a homestay specifically might contribute to the development of educators while abroad. In this article we discuss how perceived gains in Spanish proficiency, as well as increased orientation to cultural difference as measured by the Intercultural Development Inventory, were attributed to the homestay experience by preservice teachers studying in Cusco, Peru. Findings illuminate how homestays can play a positive role in educator development by providing linguistic and cultural scaffolds, as well as increased empathy for language learners.